Case Report: An innovative approach to coronary artery perforation in chronic total occlusion using autologous flaps - Chen Genrui; Wang Huan; Chen Youhu; Li Chengxiang; Gao Haokao (Frontiers in Cardiovascular Medicine)
BackgroundA percutaneous coronary intervention (PCI) for chronic total occlusion (CTO) carries a significant risk of coronary artery perforation (CAP). The typical treatment for proximal large CAP often requires the deployment of covered stents. However, this becomes impractical in situations where the antegrade wire has not successfully crossed the CTO lesion. In addition, emergency coronary artery bypass grafting for perforation after CTO-PCI is associated with a high in-hospital mortality rate.Case reportA patient presented with a left anterior descending artery (LAD) CTO involving the large first diagonal (D1) branch within the CTO segment. The D1 vessel was recanalized successfully using an antegrade approach. Before several attempts, the LAD CTO could n't be crossed, and an Ellis type Ⅲ perforation was visualized in the mid-LAD segment after bifurcation of the D1 vessel, which was created using a knuckled wire supported with a Corsair microcatheter. Subsequently, the perforation was effectively controlled by a tamponade balloon deployed from the D1 vessel to the proximal LAD. Before the retrograde wire crossed the LAD CTO, the dissection and re-entry techniques (DARTs) were used to recanalize the CTO lesion, intentionally creating subintimal dissection flaps. These autologous dissection flaps, together with drug-eluting stents instead of covered stents, successfully sealed the perforation.ConclusionThe innovative approach of using autologous dissection flaps created with DART in CTO-PCI to seal perforations is clinically feasible and effective.